Study on the hot tensile behavior, microstructure and fracture of Mg-13Gd-4Y-2Zn-0.5Zr alloy. (25th May 2018) - Meng, Mu; Che, Xin; Zhang, Zhimin; Dong, Beibei; Shi, Zheng
Abstract: The stress-strain curves of Mg-13Gd-4Y-2Zn-0.5Zr alloy are obtained by the hot tensile test at the temperature range from 400 to 520 °C and strain rate range from 0.001 to 0.5 s −1 . Then, the hot tensile behavior, microstructure and fracture characteristic are studied. The flow stress decreases with increasing temperature and decreasing strain rate, and the constitutive equation of peak stress can be expressed by an Arrhenius equation as follows: ε ̇ = 1.367 × 10 16 [ sinh ( 0.0104 σ ) ] 5.446 exp ( − 259.13/8.314 T ) . The kinking and dynamic recrystallization (DRX) are the major softening mechanisms, and the greater kinking angle and the more DRXed grains can be observed by increasing temperature and decreasing strain rate. Therefore, the strain value at fracture (SVF) is the greatest at the temperature of 520 °C and strain rate of 0.001 s −1 . The microcrack in all specimens generates at the grain boundary and the interface between the block phase and Mg matrix. And the fracture characteristic gradually develops from brittle fracture to ductile fracture with increasing temperature and decreasing strain rate.